2023
DOI: 10.2147/jir.s393600
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Binding Protein: A Prognostic Biomarker Associated with Severe or Complicated Community-Acquired Pneumonia in Children

Abstract: Purpose Heparin-binding protein (HBP) is a novel biomarker for inflammatory diseases. This study aimed to investigate the role of serum HBP in community-acquired pneumonia (CAP) in children and the association of HBP with the severity and prognosis. Patients and Methods A total of 125 children with CAP admitted to the hospital were enrolled in this retrospective study. We analyzed the differences in clinical characteristics and examination findings between patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the present study, we discovered that an elevated HBP level at admission was not significantly correlated with the length of hospital stays in CAP patients and could not be used to predict patient prognosis. Conversely, other investigations demonstrated that high HBP was strongly related with a bad outcome in CAP patients [25,26]. Different definitions of prognosis in different studies may account for this divergence, whereas in this analysis prognosis was defined as length of hospital stays.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, we discovered that an elevated HBP level at admission was not significantly correlated with the length of hospital stays in CAP patients and could not be used to predict patient prognosis. Conversely, other investigations demonstrated that high HBP was strongly related with a bad outcome in CAP patients [25,26]. Different definitions of prognosis in different studies may account for this divergence, whereas in this analysis prognosis was defined as length of hospital stays.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, HBP is primarily utilized as a potential biomarker for sepsis [39,40]. Compared to PCT and CRP, HBP exhibits earlier and more sensitive elevation, making it imperative to develop faster and more portable detection methods for this marker [41].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, approximately 740,180 children aged ≤5 years died of pneumonia ( 1 ). The incidence of CAP in children under 5 years of age in China is 65.8 per 1,000 person-years, with 12–20% of patients admitted to the intensive care unit (ICU) ( 2 ). For children with severe CAP, clinicians urgently need to identify viral or bacterial infections at an early stage to provide corresponding anti-infective treatment in time and improve poor prognosis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%